Bio-oil production via fast pyrolysis of cassava residues combined with ethanol and volcanic rock in a free-fall reactor - Koson Rueangsan; Adcha Heman; Pakkip Kraisoda; Homhuan Tasarod; Keyoon Duanguppama; Somsuk Trisupakitti; John Morris (My University, 2022)
Pyrolysis of waste biomass to produce usable energy has the potential to, in part, alleviate the consumption of limited fossil fuel resources. We describe bio-oil production via fast pyrolysis of cassava residues, a mostly wasted byproduct of cassava crops. The waste biomass was combined with two readily available additives—volcanic rock and ethanol—in a free fall reactor to generate bio-oil, char and syngas. Using cassava stems as the raw feed-stock we tested pyrolysis reaction temperatures in the range 450–500 °C in a free fall reactor using a N2 flow. Analysis of the pyrolysis products should little variation in this range, so analyses for the effects of ethanol and volcanic rock as additives were tested at 500 °C. The bio-oil yield ranged between 58 and 60%, char represented 17–19% and gas 21–24%. With volcanic rock, the higher heating value was significantly higher at 23.6 MJ/kg compared to ~19 MJ/kg for cassava alone or added ethanol. Readily available, inexpensive, naturally occuring zeolites in the volcanic rock led to significant extra degradation of the biomass, under the same experimental conditions, leading to this improvement.
Keywords: Thermochemical Biomass Conversion Processes